2013
DOI: 10.1152/physrev.00021.2012
|View full text |Cite
|
Sign up to set email alerts
|

Small G Proteins in the Cardiovascular System: Physiological and Pathological Aspects

Abstract: Small G proteins exist in eukaryotes from yeast to human and constitute the Ras superfamily comprising more than 100 members. This superfamily is structurally classified into five families: the Ras, Rho, Rab, Arf, and Ran families that control a wide variety of cell and biological functions through highly coordinated regulation processes. Increasing evidence has accumulated to identify small G proteins and their regulators as key players of the cardiovascular physiology that control a large panel of cardiac (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 592 publications
(731 reference statements)
1
80
0
Order By: Relevance
“…We demonstrated before that Rhog Ϫ/Ϫ mice do not develop hypertension (17), ruling out the implication of RhoG in Vav2-dependent roles in vascular tone regulation. It also is unlikely that such function is mediated by RhoA, given the wellknown implication of this GTPase in vasoconstriction-related vSMC responses (1). To investigate the implication of the remaining GTPases in this signaling route, we generated new mouse strains that allowed the specific, chemically inducible depletion of either Rac1 or Cdc42 in SMCs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We demonstrated before that Rhog Ϫ/Ϫ mice do not develop hypertension (17), ruling out the implication of RhoG in Vav2-dependent roles in vascular tone regulation. It also is unlikely that such function is mediated by RhoA, given the wellknown implication of this GTPase in vasoconstriction-related vSMC responses (1). To investigate the implication of the remaining GTPases in this signaling route, we generated new mouse strains that allowed the specific, chemically inducible depletion of either Rac1 or Cdc42 in SMCs.…”
Section: Resultsmentioning
confidence: 99%
“…T he dynamic regulation of the contractile behavior of vSMCs is one of the main mechanisms used by organisms to maintain blood pressure levels under both physiological and hypertensive conditions (1). Vasoconstriction is mediated primarily by pressor molecules, such as angiotensin II (AngII), catecholamines, endothelins, and eicosanoids.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the role of RhoA in vascular inflammation and atherosclerosis has not been directly addressed, evidence, mainly supported by the beneficial effect of Rho kinase inhibitors, suggested that RhoA/ Rho kinase signaling in vascular and hematopoietic cells participates in multiple steps of atherogenesis, including endothelial cell activation and dysfunction; leukocyte recruitment and cytokine and chemokine release; and oxidized LDL uptake in macrophage and foam cell formation (29). By showing a restricted role of Arhgef1 in leukocytes and in their recruitment to the endothelium, our data support the concept that RhoA GEFs discriminate upstream signals and that, depending on the cell type and the upstream activator, the RhoA GEF responsible for RhoA activation is different.…”
Section: Discussionmentioning
confidence: 99%